2009
DOI: 10.1053/j.gastro.2008.09.067
|View full text |Cite
|
Sign up to set email alerts
|

Human Equilibrative Nucleoside Transporter 1 Levels Predict Response to Gemcitabine in Patients With Pancreatic Cancer

Abstract: In this prospective randomized trial, hENT1 protein expression was associated with increased overall survival and disease-free survival in pancreatic cancer patients who received gemcitabine, but not in those who received 5-FU. These findings are supported by preclinical data; the gemcitabine transporter hENT1 is therefore a molecular and mechanistically relevant predictive marker of benefit from gemcitabine in patients with resected pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
340
2
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 407 publications
(355 citation statements)
references
References 25 publications
7
340
2
6
Order By: Relevance
“…Gemcitabine is taken up into cells primarily by human concentrative nucleoside transporter 1 and 3 (hCNT1 and hCNT3) and by human equilibrative nucleoside transporter (hENT1) [18]. The expression of these nucleoside transporters is correlated with chemosensitivity and patient survival [19][20][21][22][23]. After being taken into the cells, gemcitabine is activated by deoxycytidine (dCK) [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Gemcitabine is taken up into cells primarily by human concentrative nucleoside transporter 1 and 3 (hCNT1 and hCNT3) and by human equilibrative nucleoside transporter (hENT1) [18]. The expression of these nucleoside transporters is correlated with chemosensitivity and patient survival [19][20][21][22][23]. After being taken into the cells, gemcitabine is activated by deoxycytidine (dCK) [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of ENT1 of this tumor was elevated compared with the other 2 tumors. ENT1 is a key transporter responsible for the uptake of gemcitabine but not LY2334737, and is a biomarker for the response of patients with pancreatic cancer to Gemzar treatment (44)(45)(46). Low-dose LY2334737 treatment provided only approximately 10% of the total gemcitabine dose delivered by the gemcitabine.HCl therapy; however, elevated tumor expression of the high-affinity ENT1 transporter would enhance gemcitabine uptake, thereby arresting more cells progressing through S-phase due to prolonged systemic gemcitabine exposure.…”
Section: Discussionmentioning
confidence: 99%
“…5,30 Many studies have shown that the hENT1 but also hCNT3 expression determination can be used as a prognostic marker to provide prospective evaluations for patients receiving gemcitabine-based adjuvant therapy. 6,31,32 In L1210 murine leukaemia cells made resistant to ara-C and cross-resistant to gemcitabine, altered action of dCK can be observed, due to genomic recombination. 27 These results suggest that a partial deletion of the dCK gene observed after selection in the presence of gemcitabine is involved with resistance to this agent both in vitro and in vivo.…”
Section: Resistancementioning
confidence: 99%